Evaluation of Antioxidant Activity, Cytotoxicity, and Genotoxicity of Ptychotis verticillata Essential Oil: Towards Novel Breast Cancer Therapeutics - Mohamed Taibi; Amine Elbouzidi; Sabir Ouahhoud; El Hassania Loukili; Douâae Ou-Yahya; Safae Ouahabi; Ali S. Alqahtani; Omar M. Noman; Mohamed Addi; Reda Bellaouchi; Abdeslam Asehraou; Ennouamane Saalaoui; et al. (Life, 2023)
Breast cancer is a disease characterized by the uncontrolled proliferation of malignant cells in breast tissue, and oxidative stress activated by an accumulation of reactive oxygen species (ROS) is associated with its development and progression. Essential oils from medicinal plants, known for their antioxidant and therapeutic properties, are being explored as alternatives. Ptychotis verticillata, also known as Nûnkha, is a medicinal plant native to Morocco, belonging to the Apiaceae family, and used for generations in traditional medicine. This study focuses on the phytochemical characterization of P. verticillata essential oil (PVEO) from the province of Oujda, Morocco, for its therapeutic properties. The essential oil was obtained by hydro-distillation, and its volatile components were analyzed by gas chromatography-mass spectrometry (GC-MS). The results revealed the presence of various aromatic and terpene compounds, with carvacrol being the most abundant compound. PVEO showed antioxidant properties in several tests, including β-carotene bleaching, 2,2-diphenyl-1-picrylhydrazyl (DPPH) scavenging and total antioxidant capacity (TAC). It also demonstrated cytotoxicity against MCF-7 and MDA-MB-231 breast cancer cell lines, with higher selectivity for MDA-MB-231. The results reveal that Ptychotis verticillata essential oil (PVEO) could be a promising natural alternative for the treatment of breast cancer,